Case Study : Prognosis of Recurrent Depressive Disorder with Somatic Symptoms - Laila, Firda Nur; Algristian, Hafid; Azizah, Nur (UNUSA Press, 2023)
Introduction: Depression is a common disease worldwide, with more than 264 million people affected. Especially if it lasts a long time and is of moderate or severe intensity, depression can be a serious health condition. Depression can cause affected people to suffer greatly and function poorly at work, at school, and in the family. At its worst, depression can lead to suicide. In general, the good prognosis of depressive episodes can be achieved as well as good response to treatment and early interventions, but with the absence of any other complication such as psychotic symptoms and somatic complaints. This paper discusses the prognosis of recurrent depressive disorders with somatic complaints through a case study. Case: Male 23 years old complained of headaches that did not improve with pain medication and often recurred for two weeks, feels tingling and heavy in the back, worsening at night, interfere with the patient's daily activities and sleep in the night. These depressive symptoms have recurred since the patient was 19 years old. The patient experienced repeated stress due to arguments between his parents who were often involved in verbal abuse. The patient's prognosis is analyzed using several aspects according to Maramis prognosis analysis, including age, premorbid personality, type of disorder, course of treatment, hereditary factors, and the presence/absence of precipitating factors. Discussion: According to the course of the disease, the patient experienced recurrent depression since the age of less than 20 years, with somatic symptoms currently accompanying his depressive disorder. The patient experienced repeated recurrences even though he was stated to have improved by the treating doctor, which indicates that the patient's stress management was inadequate. The patient is currently experiencing a skin disorder that worsens his pessimistic feelings and is receiving SSRI antidepressants to improve his depressive symptoms. Based on the analysis of the course of the disease, the prognosis for depressive disorders in patients is poor, or dubia ad bonam. Conclusions: Recurrent depressive disorders involving younger ages, complications such as somatic symptoms, suboptimal social support, inadequate coping mechanisms, will worsen the prognosis of depression even after receiving adequate treatment